Evidence and Impact of Human Papillomavirus Latency - Gravitt, Patti E (Bentham Open, 2012)
At present, there is no consensus in the scientific community regarding the ability for human papillomavirus (HPV) infections to establish latency. Based on animal studies, a model of papillomavirus latency has been proposed in which papillomaviruses can be retained in the basal epithelial stem cell pool as latent infections and periodically induced to reactivate when the stem cell divides and one daughter cell is committed to terminal differentiation and induction of the viral life cycle. Tissue resident memory T-cells are hypothesized to control these periodic reactivation episodes and thus limit their duration. In this paper, evidence from human studies consistent with this model of papillomavirus latency is reviewed. Given the strong circumstantial evidence supporting a natural history of HPV infection which includes a immunologically controlled latent state, the longer term implications of HPV latency on a highly infected and aging population may warrant a more serious evaluation.